Scientific English a guide for scientists and other professionals - Day, Robert A. 1924-; Day, Nancy (Santa Barbara, Calif. Greenwood, 2011)
English language has a vocabulary of upwards of 500,000 words, it only uses nine parts of speech, and all of these words falls into one (or more) of those nine categories. This title contains many simple revelations like this that make effective scientific writing in English easy, even for those whose fluency in another language.
Principles of scientific writing -- Kinds of writing -- Writing style -- The English language -- Grammar -- Words -- Name words (nouns and pronouns) -- Action words (verbs) -- Descriptive words (adjectives, adverbs, and articles) -- Function words (conjunctions, prepositions, and interjections) -- Prefixes and suffixes -- Redundancies and jargon -- Abbreviations, acronyms, and initialisms -- Phrases -- Clauses -- Sentences -- Paragraphs -- Voice, person, and tense -- Punctuation -- Writing for electronic media -- Appendix 1 : Principles of punctuation presented plainly -- Appendix 2 : Problem words and expressions -- Appendix 3 : Words and expressions to avoid.
Keywords: English language -- Technical English -- Handbooks, manuals, etc; Technical writing -- Handbooks, manuals, etc